The application development of “Directory Connoisseur” / Marliya Mahari - Mahari, Marliya (Faculty of Information Technology and Quantitative Sciences, 2006)
This research project proposed the service application called “Directory Connoisseur’. Currently in Malaysia, fixed line phone directory are still in forms of manual books and online directories. This means users have to do manual search and this might take some times to find the appropriate address and contact numbers preferred. With the application being proposed, the manual process of directory search could be eliminates. Thus, it could saves time and provide better and faster directory search. The application developed in this thesis involves the use of SMS (Short Message Service). The SMS is the intermediate between requestor or user and the directory. Requestor will request for the preferred directory using SMS. SMS provide users with two-way communication by enabling users to request for the preferred directory in a specified format. The request then will get a response from the system. The preferred information will be send back to the requestor through SMS reply. With the use of this application, the user will have the convenience to apply it anytime and anywhere as long as the user had a mobile phone.